Germany's 2005 Welfare Reform Evaluating Key Characteristics with a Focus on Immigrants - Walter, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Physica, 2013)
In January 2005, the German government enacted a substantial reform of the welfare system, the so-called Hartz IV reform. This book evaluates key characteristics of the reform from a microeconometric perspective. It investigates whether a centralized or decentralized organization of welfare administration is more successful to integrate welfare recipients into employment. Moreover, it analyzes the employment effects of an intensified use of benefit sanctions and evaluates the effectiveness and efficiency of the most frequently assigned Active Labor Market Programs. The analyses focus on immigrants, who are highly over-represented in the German welfare system.
Introduction -- Background for the Empirical Analyses: Institutional Details and Data -- Centralized versus Decentralized Welfare Administration -- The Employment Effects of an Intensified Use of Benefit Sanctions -- The Effectiveness of Temporary Extra Jobs and Short-Term Training Programs -- Fiscal Cost-Benefit Analyses for Temporary Extra Jobs and Short-Term Training Programs -- Conclusions -- Appendices.
Keywords: Economics; Econometrics; Economic policy; Labor economics; Microeconomics; Finance; Social policy; Economics/Management Science; Labor Economics; Microeconomics; Econometrics; Public Finance & Economics; Social Policy; Economic Policy